Cor Triatriatum Dexter: A Rare Cause of Aneurysmal Right Atrium. Issue 2 (March 2022) - Patel, Mrinal; Vaidhya, Nikunj; Patel, Kartik; Sheth, Megha; Mishra, Amit
Cor triatriatum dexter (CTD) is a rare congenital cardiac anomaly with a diverse presentation in every age group. We report a case of CTD in a 36-year-old female who presented with palpitations due to giant right atrium (RA), which we managed successfully with surgical excision of the membrane and RA reduction.